Until lions learn to speak... placing the African oral tradition at the centre of power, knowledge, and media - Kennedy-Kwofie, Nana Afua (University of Cape Town, 2020)
The production of knowledge has become a matter of power rather than truth and can serve either serve as a tool of liberation or domination. This creative project seeks to explore the interaction of power, knowledge and media in Africa given its history with European colonialism. This period painted Africa as an uneducated and dark continent that had no history and no knowledge. This belief has led to assumptions about knowledge production which are embedded in racist conventions rather than the free and fair pursuit of complete knowledge. The processes of knowledge production are ranked in a hierarchy and in this system of classification, focus on the written word has dominated curriculums while other systems of knowledge production, specifically the oral tradition, have largely been undervalued and ignored. As such, what is a vibrant, complex and active tradition of African orality in the pursuit and preservation of knowledge has been relegated to the back rooms of academia and scholars are not allowed to access to a variety of methods that can be used to know and understand the world. In analysing the current climate of knowledge production and the role media plays in Africa one must examine several questions: How did the West become the centre of knowledge production? What value can be extracted from the African oral tradition in the pursuit of knowledge in the current system of knowledge production? What are the implications of this on Africans as producers of knowledge and Africa's media landscape? While this creative project does not answer these questions entirely, it opens conversations about how we understand and experience knowledge, media, and power in an African context. Guided by the frameworks of power and postcolonial theory and decolonisation, this creative project aims to offer a critical but open-ended analysis of the state of African knowledge production and media while centring the African oral tradition. This project also aims to begin the work of creating a collection of oral stories to highlight the wisdom and insight that comes from the African oral tradition and what it can offer. Ultimately, this project is a call to widen our epistemological landscapes by including African ways of knowing and media use.